2000
DOI: 10.1039/b000798f
|View full text |Cite
|
Sign up to set email alerts
|

Tautomerism of 2-hydroxynaphthaldehyde Schiff bases †

Abstract: A UV-Vis spectroscopic study based on the recently developed chemometric approach for quantitative analysis of undefined mixtures is performed on a series of donor and acceptor substituted Schiff bases of 2-hydroxynaphthaldehydes. In CCl 4 solution all compounds preferentially exist as the phenol tautomer independent of the nature of the respective substituent. With increasing polarity the tautomeric equilibrium is shifted towards the quinone form. In CHCl 3 and, especially, ethanol a clear distinction between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
125
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(132 citation statements)
references
References 32 publications
7
125
0
Order By: Relevance
“…It has been reported that it exists under azoenol (AZO) and ketohydrazone (HYZ) forms ( Fig. 1) (15)(16)(17)(18)(19)(20). In a water solution, for example, the H-atom within the O-H .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that it exists under azoenol (AZO) and ketohydrazone (HYZ) forms ( Fig. 1) (15)(16)(17)(18)(19)(20). In a water solution, for example, the H-atom within the O-H .…”
mentioning
confidence: 99%
“…The inclusion complexes of OII and CDs have been studied by several groups showing the formation of a 1:1 entity (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). So far, the CD inclusion complex studies have considered that OII in water solutions exists under AZO tautomer, contrary to many studies in solutions where OII coexists under AZO and HYZ forms (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Recently, ultrafast transient lens technique with a response function of Ϸ300 fs has been used to study the dynamics of OII in CD (36).…”
mentioning
confidence: 99%
“…Tautomerism in 2-hydroxy Schiff bases both in solution and in the solid state was investigated using different spectroscopic techniques [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. In the spectra of solutions of these compounds different Schiff bases have been studied in both polar and non-polar solvents [5,6,8,9,11,13,16,20]. A new band at greater than 400 nm has been observed in polar solvents, and in acidic media in some solvents, but this band has not been observed in hydrocarbon solvents.…”
Section: Introductionmentioning
confidence: 99%
“…2-Hydroxy Schiff base ligands and their complexes, derived from the reaction of salicylaldehyde and 2-hydroxy-1-naphthaldehyde with amines have been extensively studied [1][2][3][4][5][6]. 2-Hydroxy Schiff base ligands are of interest mainly due to the existence of (O-H···N and N-H···O) type hydrogen bonds and tautomerism between the enol-imine and keto-enamine forms (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…As an example, 13 C-NMR data related to compound II are given below (The result were given as regards to It is known that 2-hydroxy Schiff bases interact with polar solvent molecules in protic media. [29][30][31] Here, the solvent molecules act as both proton donors and proton acceptors, and form a keto structure through a Zwitterion, as depicted in Scheme 1. 31 Starting from the CV data and this fact, the following pathway is proposed for the electrochemical reduction of Schiff bases (Scheme 2).…”
Section: Controlled-potential Preparative Electrolyses and Mechanism mentioning
confidence: 99%